IMPLEMENTASI MODEL PJBL PADA MATERI LARUTAN ELEKTROLIT DAN NONELEKTROLIT TERHADAP KREATIVITAS SISWA - Fahmi Adnan; Rody Putra Sartika; Rahmat Rasmawan (Universitas Tanjungpura, 2021)
AbstractThis study aimed to describe the creativity of a group of students at SMA Negeri 5 Pontianak who were taught used a project-based learning model on electrolyte and nonelectrolyte solution material in terms of designing student projects and aspects of displaying student project results. The research method was pre-experimental design. The research design used was a one-shot case study. The research subject was taken by purposive sampling technique. The subjects in this study were students of class X IPA1 SMA Negeri 5 Pontianak. The data collection technique was done by used measurement techniques. The data collection tool was carried out with a rubric for assessing student creativity. The results of the study obtained a value in the design aspect of project creation with a percentage of 65.47%, the criteria was creative enough and in the aspect of displaying the project results obtained a percentage of 78.55% for the creative criteria.Keywords: Creativity, Electrolyte and Non-Electrolyte Solutions, Project Based Learning